ADVANTAGES AND CHALLENGES OF IMPLEMENTING REPRODUCTIVE BIOTECHNIQUES IN THE WEST GOIANO DAIRY APL - Rodrigues Andrade, Weverton; Ferreira de Oliveira, Gabriel; Althair Ribeiro Cordeiro, Fábio; Aurélio Souza Ramos, Marco; Teixeira da Silva, Jhonata; Pedro Pinheiro dos Santos, João; José Gonçalves dos Santos, Klayto (Journal of Interdisciplinary Debates, 2023)
Considering the current market for cattle farming, it is necessary to implement reproductive technologies and biotechnologies on a property. In this sense, BIOTEC activities to bring these biotechnologies to small producers in APL Oeste, this work aims to show the main benefits and difficulties encountered in this implementation. These highlighted benefits and difficulties are based on the experience of the institution’s veterinarians and interns during activities on APL Oeste properties, in terms of what else is needed both to improve results after the implementation of biotechnologies, and productivity itself. The difficulties of a structural, nutritional and management nature are highlighted, and the main benefits are the genetic improvement and zootechnical control of animals, which shows that there is still a lot to improve so that these activities can reach more producers and improve their results in those that are already in the project.